The Effectiveness of IndiBiz Marketing Strategy in Building Interest and Purchasing Decisions for Business Internet Services in the MSME Segment in the Yogyakarta Region and Surrounding Areas - Bayu Andrian; Fadhilla, Hanifa Nur (JURNAL MANAJEMEN MOTIVASI, 2026)
This study explores the effectiveness of PT Telkom Indonesia’s IndiBiz marketing strategy in influencing SMEs’ purchase intentions in Yogyakarta. Through interviews with five business owners and field observations, the study finds that competitive pricing, promotions, and brand image build consumer trust. However, competitors offer more flexible pricing and features. The results suggest IndiBiz should enhance educational promotions, service quality, and targeted marketing. Future research should involve larger samples and a mixed-method approach to better assess IndiBiz’s digital marketing effectiveness across regions and SME segments.